2017
DOI: 10.4314/sajg.v6i3.1
|View full text |Cite
|
Sign up to set email alerts
|

Large scale mapping: an empirical comparison of pixel-based and object-based classifications of remotely sensed data

Abstract: In the past, large scale mapping was carried using precise ground survey methods. Later

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Nowadays, the data obtained from Earth Observing Systems such as Sentine-2, Landsat-7, Landsat-8, EOS AM-1 can be used for agricultural purposes [3], they provide multispectral images with spatial resolutions from 10 meters to 250 meters. However, the images obtained from these spacecraft do not allow the creation of large-scale maps (1: 25000 and 1: 10000) of relatively small land plots (for example, farms) [4,5]. Studies have shown the feasibility of using satellite images of very high spatial resolution (≥0.5 m) for the creating and updating of large-scale maps, in terms of accuracy, reliability and efficiency [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the data obtained from Earth Observing Systems such as Sentine-2, Landsat-7, Landsat-8, EOS AM-1 can be used for agricultural purposes [3], they provide multispectral images with spatial resolutions from 10 meters to 250 meters. However, the images obtained from these spacecraft do not allow the creation of large-scale maps (1: 25000 and 1: 10000) of relatively small land plots (for example, farms) [4,5]. Studies have shown the feasibility of using satellite images of very high spatial resolution (≥0.5 m) for the creating and updating of large-scale maps, in terms of accuracy, reliability and efficiency [6,7].…”
Section: Introductionmentioning
confidence: 99%